2016
DOI: 10.5539/ies.v9n8p134
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Writing Apprehension and Writing Performance: A Qualitative Study

Abstract: <p class="apa">Writing skill is seen as a cornerstone of university students’ success in both academic and career life. This qualitative study was conducted to further explore the teachers’ and students’ perceptions on the relationship between writing apprehension and writing performance, contributing factors of writing apprehension, and strategies to reduce writing apprehension. Semi-structured interviews were conducted to get more in-depth information from two respondents: one experienced instructor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Al-Shboul & Huwari (2015) found that learners who had bad experience about writing in their past, end up having higher writing apprehension. In addition to that, Badrasawi, Zubairi & Idrus (2016) also found that writing apprehension can lead to poor performance in that skill. Hence, this study is done to explore the cycle of fear in writing and how learners are coping with that.…”
Section: Introductionmentioning
confidence: 83%
“…Al-Shboul & Huwari (2015) found that learners who had bad experience about writing in their past, end up having higher writing apprehension. In addition to that, Badrasawi, Zubairi & Idrus (2016) also found that writing apprehension can lead to poor performance in that skill. Hence, this study is done to explore the cycle of fear in writing and how learners are coping with that.…”
Section: Introductionmentioning
confidence: 83%
“…Other major factors that led to writing anxiety was lack of the ability to organize and express their ideas (Badrasawi, Zubairi, & Idrus, 2016). As a result, anxiety undermines the ability to think cohesively (Onwuegbuzie, 1997).…”
Section: Learners' Perceptions On Efl Writing Practicesmentioning
confidence: 99%
“…Among miscellaneous problems, limited time still exists as a paramount obstacle for them to writing practices (Pujianto, Emilia & Ihrom, 2014, Turmudi, 2017. Badrasawi, Zubairi and Idrus (2016) maintained that writing apprehension contributes negatively to students' writing performances, notably in ESL context. Another problem generates from the language transfer from their L2 (Bahasa Indonesia) to the target language (English) while they write in foreign language context (Tandiana, et.…”
Section: Pjee -------------------------------------------------------mentioning
confidence: 99%